THE ROLE OF MODERATING EFFECT OF SOCIAL DEMOGRAFY TO FINANCIAL LITERACY , SELF CONTROL , AND RISK TOLERANCE ON FINANCIAL BEHAVIOR SHOPEE USER PAYLATER IN DIY - Sujoko, Sujoko; Najwa, Najwa; Suherli, Suherli (International Journal of Social and Management Studies, 2025)
The development of paylater services such as Shopee PayLater brings new challenges in personal financial management. This study aims to analyze the effect of financial literacy, self-control, and risk tolerance on the financial behavior of Shopee PayLater users in DIY , and test the role of social demography as a moderating variable. This research uses a quantitative approach with a survey method of 380 respondents who are active users of Shopee PayLater. The research was conducted for months from July through October 2023. The analysis technique used was Structural Equation Modeling Partial Least Square (SEM-PLS) and Multi Group Analysis (MGA). The results show that financial literacy, self-control, and risk tolerance have a positive and significant effect on financial behavior. In addition, social demographics proved to moderate the relationship between the three independent variables and financial behavior. These findings provide important implications in increasing financial awareness and risk management in the use of PayLater services, especially for certain demographic groups.The study still has limitation that financial behavior scope user pay later in DIY, Future research to expand this scope in Central Java.